Perjanjian Kerjasama Segitiga Indonesia-Malaysia-Thailand (IMT-GT) dalam Bidang Pendidikan di Sumatera Utara - Bina Era Dany (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
Along with the enactment of the Law no. 32 of 2004 concerning Regional Government, Sub-regional Economic Cooperation IMT-GT is expected to be one of the modalities to encourage the initiatives and the active participation of local communities in increasing the empowerment of educational potential in their respective regions.The position of the triangle cooperation agreement of Indonesia, Malaysia, Thailand (IMT-GT) in the field of education contributes to the IMT GT participating countries to carry out the activities as agreed in the IMT GT activities. The position of IMT-GT also provides a position of convenience for IMT-GT participating countries to make efforts to improve the education, both through student and teacher exchanges as well as the repair and the procurement of the school facilities and infrastructure.The regulated matters in the triangle cooperation agreement of Indonesia, Malaysia, Thailand (IMT-GT) are basically not in the field of education but in the economic field. The existence of the world of education has a relationship with the implementation of the IMT-GT program because the running of the economic program will provide a feedback to the development of the world of education.The obstacles of the triangle cooperation agreement of Indonesia, Malaysia, Thailand (IMT-GT) in the field of education are the difficulty of obtaining permits in Indonesia, uncertain political conditions and the unfavorable conditions of labor life. This condition has an impact on the lack of the desire of entrepreneurs from IMT-GT participating countries to invest in Indonesia, thus giving an impact to the improvement of the education system. Keywords : Agreement, Cooperation, Education